The Role of Connexin in Cutaneous Adverse Drug Reactions (CADRs) in Patients with Increasing Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) - Dyah Ayu Mira Oktarina; Gilang Baswara; Hardyanto Soebono (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: The occurrence of Cutaneous Adverse Drug Reactions (CADRs) is relatively rare but can be fatal when causing organ failure, especially in the liver. The supporting examinations to determine liver injury are aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Connexin-32 (Cx32) and connexin-43 (Cx43) are gap junction proteins that can be found in the liver and allegedly have a role in the mechanism of liver injury. To date, correlations between the level of connexin and aminotransferases enzyme in humans with CADRs cases are still unclear. Purpose: To determine the correlations between Cx32/Cx43 and AST/ALT levels in CADRs cases. Methods: This was a retrospective study, data collected from inpatient and outpatient’s medical records, Department of Dermatology and Venereology of Dr. Sardjito Hospital, from 2011–2015. Result: A total of 25 patients with CADRs and 35 healthy controls were included in this study. The levels between Cx32 and AST, Cx32 and ALT, Cx43 and AST, and Cx43 and ALT were not significantly correlated in CADRs cases (p>0.05). Both Cx32 and Cx43 were not significantly different between patients with and without CADRs (p>0.05). Confounding factors such as gender were not associated with this study (p>0.05). Conclusion: There was no correlation between levels of Cx32/Cx43 and increasing AST/ALT in CADRs cases. Therefore, further study is necessary to conclude the correlation between connexin and aminotransferase enzyme in CADRs patients.